STRUCTURE OF A COMPUTER PROGRAM FOR DETERMINING THE OPTIMAL PATH DIRECTED GRAPH USING DIJKSTRA'S ALGORITHM - SHCHERBAN, Volodymyr; ISHCHENKO, Valentin; KOLISKO, Oksana; MELNIK, Genadij; SHCHERBAN, Yuryj (Herald of Khmelnytskyi National University. Technical sciences, 2022)
Ensuring the minimum tension during thread processing on technological equipment allows to reduce equipment downtime due to the elimination or significant reduction of thread breaks. Minimization of tension is ensured by optimization of the shape of the thread filling line, in which the total angle of coverage of the guides will be minimal. This problem is solved by using Dijkstra's algorithm in finding the optimal path of a directed graph. The computer program for implementing this algorithm allows you to optimize the form of filling the thread on the technological equipment. The development of application packages of computer programs allows to reduce the time for the design of technological processes in the light and textile industry as much as possible. This is due to the modernization of the thread filling line on the technological equipment, which allows to minimize thread tension in the working area. Minimization of tension is ensured by optimization of the shape of the thread filling line, in which the total angle of coverage of the guides will be minimal.This problem is solved by using Dijkstra's algorithm in finding the optimal path of a directed graph. Construction of the optimal path of the directed graph will allow to obtain the minimum tension in the working area. Constructive structural elements in the form of guides, elements of tensioning devices, break control devices, which have a cylindrical, elliptical shape, and discrete segments of a straight line act as obstacles in the path of the thread. Straight line segments can have an inclination relative to the vertical axis. Taking into account the large number of structural elements of the thread feeding system on light and textile industry machines and their location, there is a need to develop a special computer program for determining the optimal shape of the thread feeding line using the Dijkstra algorithm when searching for the optimal path of a directed graph.The objective function in the problem is the minimum necessary tension, which is the minimum sum of the angles covered by the thread of guide surfaces that have a cylindrical, elliptical shape, discrete segments of a straight line. The use of a computer program allows you to determine tensions and changes in relative tension in the filling zones of light and textile industry machines, which allows you to optimize the shape of the thread supply line even at the stage of designing the technological process. The use of algorithms for computer programs for finding the optimal path of an undirected graph, for cylindrical, elliptical guides, discrete segments of a straight line, allows you to determine the influence of coverage angles on the target tension function. Determining the effect of coverage angles, for cylindrical, elliptical guides, discrete segments of a straight line, on the objective function during the computer determination of the optimal path for an oriented graph is an important component of the optimization of thread tension in the working area of machines of the light and textile industry, the formation of knitted and textile products.
Keywords: computer program; optimal path; directed graph; Dijkstra's algorithm